Teaching Uzbek Folk Music to Students Studying Music in Higher Education - Z. Ziyavutdinova (International Journal on Integrated Education, 2021)
Today Uzbek folk music is taught to students of higher educational institutions in the field of art. Students will witness the richness of the culture of the Uzbek people, the history of the origin of its folk songs and melodies, the fact that over the years all these melodies and songs have found their way and improved. Also the founders of the folk song: Y. Radzhabiy, Uspensky, Romanovsky and others made their contribution, the composer's work is very rich, students will have an idea that composing was developed with great difficulty. Using the examples of Uzbek folk art, students understand not only the culture of Uzbek music and art, but also its educational value.